1982
DOI: 10.1139/f82-057
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Studies of Arctic Cod (Boreogadus saida) in Beaufort Sea Coastal Waters, Alaska

Abstract: Fish use of Beaufort Sea coastal waters was examined during summer and winter periods 1977–80. Arctic cod (Boreogadus saida) were abundant but their occurrence was highly variable. They accounted for 8–78% of all fish caught in Simpson Lagoon during two summers, and 0.4–100% of catches at various coastal sites in winter. Arctic cod increased in abundance in the lagoon during late summer and some association was noted between their numbers and higher salinities but not temperature or turbidity. Some cod remaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
101
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(109 citation statements)
references
References 0 publications
7
101
1
Order By: Relevance
“…Results of tagging studies show that white whales can dive to depths of more than1000 m and exhibit behaviors indicative of foraging at depths of several hundred metres (Martin et al, 1993). Conversely, Craig et al (1982) reported arctic cod abundance increased during late summer in an ice-free lagoon located along Alaska's north-central coast. Selection of ice-free habitat by some white whales in summer may be a response to foraging opportunities in nearshore waters, or habitat desired for skin molting, or both (Frost and Lowry, 1990).…”
Section: Seasonal Habitats and Trophic Relationshipsmentioning
confidence: 92%
“…Results of tagging studies show that white whales can dive to depths of more than1000 m and exhibit behaviors indicative of foraging at depths of several hundred metres (Martin et al, 1993). Conversely, Craig et al (1982) reported arctic cod abundance increased during late summer in an ice-free lagoon located along Alaska's north-central coast. Selection of ice-free habitat by some white whales in summer may be a response to foraging opportunities in nearshore waters, or habitat desired for skin molting, or both (Frost and Lowry, 1990).…”
Section: Seasonal Habitats and Trophic Relationshipsmentioning
confidence: 92%
“…More recent work reported normal fry development between ¡1.5 and 3.0°C, but highest survival rates occurred between 0.5 and 3.0°C (Sakurai et al 1998), observations supported by Fortier et al (2006). In coastal waters, adults occasionally tolerate temperatures as warm as »13°C, albeit they are more commonly found in waters no warmer than 6-7°C (Craig et al 1982).…”
Section: Introductionmentioning
confidence: 92%
“…[175] They represent an important energy and Hg link between the base of sea ice food webs and higher trophic level predators that include Arctic cod (Boreogadus saida), ringed seals (Phoca hispida) and birds. [176][177][178][179][180][181] Gammarids in Lancaster Sound had Hg concentrations of 0.1 mg g À1 DW. [146] Arctic cod are thought to be a keystone species linking under ice food webs to many marine mammals and birds.…”
Section: Bottom Upmentioning
confidence: 99%